Attitudes of tenth grade students in Jordan towards vocational education - AL-Momani, Mohammad Omar; Rababa, Elham Mahmoud (Intelektual Pustaka Media Utama, 2025)
This study aims to identify tenth grade students’ attitudes towards vocational education in Jordan, as well as this attitude’s relationship with the gender variable. The analytical descriptive approach was used to achieve the goals of this study. A questionnaire consisting of 25 items was created covering six fields: the professional field, the administrative field, the health field, the economic field, the media field, and the educational field. This questionnaire was distributed to a sample of 1,184 male and female students in the schools of the Jordanian Ministry of Education in the first semester of the academic year 2022/2023. After conducting the appropriate statistical treatments to tenth grade students’ attitudes towards vocational education in Jordan, the results were a medium degree of correlation on the tool as a whole and on all of the areas of study mentioned. There was a lack of statistically significant trends within a 95% confidence interval α≤0.05 for the gender variables (male and female students).